2012
DOI: 10.1007/s00417-011-1919-y
|View full text |Cite
|
Sign up to set email alerts
|

Systemic corticosteroids reduce the risk of cellophane membranes after retinal detachment surgery: a prospective randomized placebo-controlled double-blind clinical trial

Abstract: Early stages of PVR such as cellophane membranes after retinal detachment surgery can be reduced with corticosteroids in oral doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
1
28
0
2
Order By: Relevance
“…Another reason could be a biphasic effect of steroids, which are stimulatory on RPE cell proliferation at lower concentrations and inhibitory at higher concentrations 21. However, previous studies have shown that steroids reduce postoperative inflammation22 23 or reduce the risk of cellophane membranes after RD surgery 24…”
Section: Discussionmentioning
confidence: 99%
“…Another reason could be a biphasic effect of steroids, which are stimulatory on RPE cell proliferation at lower concentrations and inhibitory at higher concentrations 21. However, previous studies have shown that steroids reduce postoperative inflammation22 23 or reduce the risk of cellophane membranes after RD surgery 24…”
Section: Discussionmentioning
confidence: 99%
“…Both strategies of retinopexy induce a pro-inflammatory environment that could explain the high risk as shown in experimental models Goldaracena et al, 1997;Pinon et al, 1992). Indeed, in a prospective, randomized, placebo-controlled, double-blind clinical trial performed to determine if prolonged administration of systemic corticosteroids would attenuate early stages of PVR, the application of transcleral cryocoagulation was associated with more cases developing epiretinal membranes in the placebo than the steroid group (Koerner et al, 2012). These findings reinforce the idea that the anti-inflammatory strategy could be one of the best options for preventing PVR.…”
Section: Preoperative Intraoperative and Postoperative Risk Factorsmentioning
confidence: 99%
“…10 Oral steroid intakes that supposedly suppress TGF-b activity did not robustly contribute to the prevention of PVR in surgical RD cases. 11,12 Therefore, a better understanding of the precise mechanism and the discovery of a novel therapeutic target for PVR is necessary.…”
mentioning
confidence: 99%